THE RELATIONSHIP BETWEEN THE HIGH OF FUNDUS UTERI WITH THE BABY WEIGHT DURING LABOR IN GENERAL HOSPITAL UMI BAROKAH BOYOLALI - KLATEN, STIKES DUTAGAMA (STIKES DUTAGAMA KLATEN, 2013)
Background : Based on the survey in General Hospital Umi Barokah Boyolali on March 26, 2012 , shows the majority of mothers delivered has a high of maternal fundus 34 cm with the birth weight 2800 grams , if the estimated fetal weight was 3565 grams calculated, and there is a high maternal fundus which had 31 cm with birth weight 3750 grams if the estimated fetal weight was calculated 3100 grams. So there is a discrepancy between the estimated of fetus birth weight with birth weight babies.Objective: To determine the relationship between the height of fundus uteri with birth weight during delivery in public hospitals Umi Barokah Boyolali .Research Methodology : This study is using the quantitative analytical studies using correlational and cross-sectional approach . Sampling using accidental sampling . Samples were taken as many as 44 samples that met the inclusion criteria.   Results : Based on the results of statistical tests using Pearson Product Moment formula with a confidence level of 95 % was obtained count r (correlation coefficient ) is 0.393 , which means a low -level ties . Results r count than r table , the count r ( 0.393 ) > from table r (0.297 ) , so that Ho is rejected and Ha accepted . Then there is a positive relationship with the low -level relationship between uterine fundus with birth weight , so the higher of the fundus , the heavier the baby weight during born. TFU great influence on birth weight by 15 % .   Conclusion : Statistically, there is a positive relationshipwith a low -level ties between the high of fundus uteri with the baby weight during delivery in public hospitals Umi Barokah Boyolali .